2014
DOI: 10.3402/edui.v5.23924
|View full text |Cite
|
Sign up to set email alerts
|

The significance of place and pedagogy in an urban multicultural school in Sweden

Abstract: This article presents research from a school in a multicultural suburb on the outskirts of a large Swedish conurbation that used a particular pedagogy with strong classification and framing to address an identified problem of academic failure amongst its pupils. The analysis shows that the pedagogy was chosen based on an assumption that pupils needed to be 'saved' from their backgrounds and assumed characteristics of their neighbourhood and that its inhabitants were lacking positive pedagogical resources. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Multicultural schools in socially deprived areas are often initially described in positive terms by their actors, including school professionals and students (Bunar, 2009, 2010; Schwartz, 2014). These actors often emphasize that the school itself, with its current student body, and in contrast to negative perceptions and rumors, is just another ordinary school.…”
Section: ‘It’s All About Immigrants’mentioning
confidence: 99%
See 1 more Smart Citation
“…Multicultural schools in socially deprived areas are often initially described in positive terms by their actors, including school professionals and students (Bunar, 2009, 2010; Schwartz, 2014). These actors often emphasize that the school itself, with its current student body, and in contrast to negative perceptions and rumors, is just another ordinary school.…”
Section: ‘It’s All About Immigrants’mentioning
confidence: 99%
“…However, an important distinction must be made: the reputation of Bridge Valley School was almost completely dominated by perceptions of its urban space, while in the cases of the two other schools, middleclass and with largely Swedish populations, urban spaces were acknowledged as important but not definitive. In other words, urban spaces do not completely overshadow the schools' internal Multicultural schools in socially deprived areas are often initially described in positive terms by their actors, including school professionals and students (Bunar, 2009(Bunar, , 2010Schwartz, 2014). These actors often emphasize that the school itself, with its current student body, and in contrast to negative perceptions and rumors, is just another ordinary school.…”
Section: Novamentioning
confidence: 99%
“…Learners staying outdoors are often surrounded by and provided with more abundant learning stimuli in nature, such as smells, colors in nature, different textures of plants, etc. Häggström and Schmidt (2020) found that direct encounters with the outdoor environment enhanced children's basic literacy and ecological literacy, which further helps to develop critical thinking, consistent with the effects of outdoor place-based learning (Schwartz, 2014). The above research indicated a place-based pedagogy started to impact the way of learning, which highlights a democratic and independent learning environment for learners (McInerney et al, 2011).…”
Section: Outdoor Place-based Pedagogy For Englishmentioning
confidence: 55%
“…Previous research in Scandinavian countries has suggested that outdoor settings make subject-related learning for young learners potentially more meaningful (Schwartz, 2014;Sjöblom & Svens, 2019) as staying outdoors was more an interest-oriented and experience-centered instructional strategy (Sheppard, 2011) and most likely helped learners engage in more active inquiry practices (Ireland et al, 2014) where more connections to students' life experiences were made and social interaction was encouraged (Tal, 2016). Learners staying outdoors are often surrounded by and provided with more abundant learning stimuli in nature, such as smells, colors in nature, different textures of plants, etc.…”
Section: Outdoor Place-based Pedagogy For Englishmentioning
confidence: 99%